1982
DOI: 10.1104/pp.70.1.113
|View full text |Cite
|
Sign up to set email alerts
|

A Thioredoxin-Mediated Activation of Glutamine Synthetase and Glutamate Synthase in Synchronous Chlorella sorokiniana

Abstract: The effects of thioredoxin, dithioerythrol, and mixtures of both on enzymes involved in N metabolism of Chlorella sorokiniana have been studied. Glutamine synthetase, inactivated in vivo, was activated 8-fold by thioredoxin and dithioerythrol. By the same treatment, the activity of glutamate synthase was stimulated nearly 4-fold. Thus, two key enzymes of N metabolism were shown to be regulated via thioredoxin. The enzymes of the nitrate reducing system, i.e. nitrate reductase and nitrite reductase, were not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 11 publications
2
15
1
Order By: Relevance
“…Since GS, and GS,, show very similar characteristics, it is concluded that the location of GS,, in the chloroplast rather than any alteration of its catalytic properties renders it more efficient in detoxifying NH3 than GS,, which is present in the cytosol (15). In chloroplasts, reduced thioredoxins are present which markedly activate GS in Chlorella (22). As previously discussed (2), it seems more logical that GS, might play a major role in the reassimilation ofphotorespiratory produced ammonia.…”
Section: Discussionmentioning
confidence: 72%
“…Since GS, and GS,, show very similar characteristics, it is concluded that the location of GS,, in the chloroplast rather than any alteration of its catalytic properties renders it more efficient in detoxifying NH3 than GS,, which is present in the cytosol (15). In chloroplasts, reduced thioredoxins are present which markedly activate GS in Chlorella (22). As previously discussed (2), it seems more logical that GS, might play a major role in the reassimilation ofphotorespiratory produced ammonia.…”
Section: Discussionmentioning
confidence: 72%
“…Total GS activity was independent of applied 02 tensions, however. Recently it was observed that thioredoxin activates GS and glutamate synthase of C. sorokiniana (20). A difference in intracellular levels ofreduced thioredoxin might thus also result in a different capacity for the assimilation of NH3 produced during photorespiration.…”
Section: Materiais and Methodsmentioning
confidence: 99%
“…Under these growth conditions the photorespiratory NH3 production is maximal. GS,, may be more effective in assimilating NH3 produced during photorespiration than GS, due to its higher affinity for glutamate (16) or due to its localization in the chloroplast where thioredoxins are present which activate the C. sorokiniana enzyme (20).…”
Section: Materiais and Methodsmentioning
confidence: 99%
“…Ketol acid reductoisomerase was previously reported as a potential target in cereal seeds (Wong et al, 2004b), phosphoglycerate dehydrogenase in spinach chloroplasts , and Gln synthetases in C. reinhardtii and Arabidopsis (Motohashi et al, 2001;Lemaire et al, 2004;Marchand et al, 2004;Yamazaki et al, 2004). The activity of both chloroplastic and cytosolic isoforms of Gln synthetase have long been known to be activated by Trx (Tischner and Schmidt, 1982;Florencio et al, 1993). The cytosolic isoform was found to undergo reduction in germinating M. truncatula seeds in this study.…”
Section: Amino Acid Synthesismentioning
confidence: 99%